2021
DOI: 10.1002/jmv.27106
|View full text |Cite
|
Sign up to set email alerts
|

Does the COVID‐19 seroconversion in older adults resemble the young?

Abstract: High antibody titers have been found to correlate with the severity of coronavirus disease 2019 (COVID‐19) disease. Therefore, antibody titers may be higher in older adults, whose disease is known to have a more severe course than younger ones. This study aimed to compare the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) immunoglobulin G (IgG) antibody level in the reverse transcription‐polymerase chain reaction (RT‐PCR) to test positive older adults with young. Patients aged ≥18 with positive R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
5
2
1
Order By: Relevance
“…In our previous study, the antibody levels measured with the same method (IFA) at the third month after positive RT-PCR in older adults who had COVID-19 disease (53.3 ± 13.4) were higher than the antibody levels at the first month after vaccination for both vaccine groups in the current study (CoronoVac: 25.9 ± 8.6, Pfizer-BioNTech: 36.6 ± 15.4). 13 In contrast to our studies, the receptor-binding domain (RBD)-binding IgG concentrations in the Pfizer-BioNTech vaccine study were found to be above those seen in serum from a group of individuals recovering from COVID-19 (mean titers of antibodies on Day 43 were 0.7-fold (1-μg dose) to 3.5-fold (50-μg dose) those of the recovered individuals). 6 In our study in older adults, the opposite was the case, suggesting that recovering from the disease in older adults creates higher immunity than vaccination.…”
Section: Discussioncontrasting
confidence: 99%
“…In our previous study, the antibody levels measured with the same method (IFA) at the third month after positive RT-PCR in older adults who had COVID-19 disease (53.3 ± 13.4) were higher than the antibody levels at the first month after vaccination for both vaccine groups in the current study (CoronoVac: 25.9 ± 8.6, Pfizer-BioNTech: 36.6 ± 15.4). 13 In contrast to our studies, the receptor-binding domain (RBD)-binding IgG concentrations in the Pfizer-BioNTech vaccine study were found to be above those seen in serum from a group of individuals recovering from COVID-19 (mean titers of antibodies on Day 43 were 0.7-fold (1-μg dose) to 3.5-fold (50-μg dose) those of the recovered individuals). 6 In our study in older adults, the opposite was the case, suggesting that recovering from the disease in older adults creates higher immunity than vaccination.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study are in line with those obtained by Soytas et al, 6 who found that antibody titers were higher in the age group over 80 years, compared to the younger group (≥ 18 and < 60 Years). In the study, efforts were made to compare the level of IgG antibodies in confirmed SARS-CoV-2 patients with RT-PCR.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, there were large differences in the spike-binding antibody titers across participants with those 40 years and older having higher antibody titers compared to younger individuals. This phenomenon has been observed before (19,20). Our observation that female participants have higher antibody titers than male participants stands in contrast to several previous studies reporting that males have higher SARS-CoV-2 antibody levels (4).…”
Section: Discussioncontrasting
confidence: 83%
“…We found that more advanced age (e.g., 40 years or older) was associated with 1.62-fold higher antibody levels (95% CI: 1.20-2. 19) compared to younger participants. Sex was also associated with the level of SARS-CoV-2 spike antibodies, with antibody levels being 1.40-fold higher in female participants (95% CI: 1.03-1.92) than male participants (Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 82%